Reforming the Labor Administration in Bhutan - Wangda, Pema (World Bank, Washington, DC, 2012)
At the end of a long reform process, Bhutan adopted the labor and employment act of Bhutan on January 5, 2007. The act constitutes the first comprehensive labor market legislation adopted in Bhutan. As part of a wider reform of labor administration policy, it is a major step in the modernization of the country's labor market. The new law mandates a certain minimum level of occupational health and safety standards and establishes a comprehensive inspection regime to enforce them. It also improves the bargaining position of workers vis-a-vis employers, allowing them for the first time to organize at the enterprise level. Moreover, the act achieves this without introducing rigidities that might hamper employment growth. The reform was essential to accommodate emerging social trends, such as growing rural-urban migration, the high rate of population growth, and the resulting increase in unemployment. The author aim is to channel the expanding labor force into the private sector, and the author therefore had to make employment in the private sector more desirable. The author expects these changes to encourage private sector development, stimulate entrepreneurship, and lead to more job creation.